RUMAH GADANG SEBAGAI LAMBANG DEMOKRASI SUKU MINANGKABAU DI SUMATERA UTARA - Muhammad Azhar Faturahman; Muhammad Yusvado A H; Silvia Rini Putri (Jurnal Soshum Insentif, 2021)
Abstract – The ethnic of Minangkabau is known for their competency in implementing social and cultural values. Minangkabau is one of the ethnic that is upholding egalitiarian and democracy system. One of their cultures related is deliberation to achieve consensus within the community. The deliberation process is done stagely by holding conferences inside one of their custom houses or known as gadang house. Gadang house is very symbolic to the Minangkabau ethnic and carries important social and cultural values. As is well known, deliberation or discussion has an important role in Indonesia’s democracy system. This study aims to discuss and discover the meaning and values behind Minangkabau’s custom house and how it impacts the effectiveness of the deliberation process by its relevance as a symbol to represent democracy values in the Minangkabau community. The method used in this study is descriptive analysis by performing literature study. According to the result of the study, authors expect to expand insight and knowledge of Indonesian people with Minangkabau culture and its implementation of democracy values in daily life. Abstrak – Masyarakat suku Minangkabau dikenal sebagai salah satu suku yang memiliki menjunjung tinggi nilai-nilai sosial dan budaya. Salah satu kebudayaan masyarakat suku Minangkabau yang erat kaitannya dengan demokrasi adalah pelaksanaan musyawarah untuk mufakat dalam. Musyawarah oleh masyarakat Minangkabau dilakukan secara bertahap dan dalam beberapa pertemuan di rumah adat gadang atau balai adat. Dalam konsep demokrasi di Indonesia, musyawarah merupakan hal yang tidak dapat dipisahkan. Penelitian ini bertujuan untuk mengetahui makna dari rumah adat gadang serta seberapa besar pengaruhnya sebagai lambang yang merepresentasikan nilai-nilai demokrasi pada masyarakat Minangkabau. Metode yang digunakan dalam penelitian ini adalah deskriptif analisis dengan melakukan studi literatur. Dari hasil penelitian yang sudah dilakukan, penulis berharap dapat menambah wawasan dan ilmu pengetahuan kepada masyarakat Indonesia akan kearifan budaya Nusantara dalam menjalankan demokrasi di dalam kehidupan sehari-hari.